THE STRUCTURE OF SUPPORT DESIGN DECISIONS SYSTEM DURING THE DESIGNING OF GLASS UNIT - Lisnevskyi, R. V. (Science and Transport Progress, 2006)
The article determines basic factors and characteristic features in the project decision-making process in designing glass packages, which generate the task of its improvement. The basic way of its solution is considered, in the quality of which a system of project decisions support is offered. The list of basic functions of the project decisions support system, based on the analysis of the designer’s activity structure at selecting the option of project decision, is offered for consideration. The developed structure is rather flexible and universal, which allows to use it for solving the designing tasks. Realization of the offered approach will allow to improve the quality of project decisions and efficiency of designing the glass packages in constructional structures.